A Research on Blockchain Technology: Urban Intelligent Transportation Systems in Developing Countries - Xingcheng Guo; Xianglong Guo (IEEE Access, 2023)
Blockchain technology has been widely used in finance, transportation, education, medical treatment, network security, management science, and other industries due to its decentralization, high reliability, and traceability characteristics. Unlike other studies on Urban Intelligent Transportation Systems (UITS) in the past, we present a model framework of the Urban Intelligent Transportation Systems (UITS) applied by blockchain in developing countries. After a detailed elaboration of the situation of three representative Urban Intelligent Transportation Systems (UITS) in China, blockchain technology has been applied to build a new architecture model of the big data platform for urban intelligent transportation, as well as the design concept and conceptual model for the new generation of the Urban Intelligent Transportation Systems (UITS) in developing countries. Finally, this paper elaborates on the critical direction of future development, areas of concern, and open research challenges, which researchers and urban intelligent transportation designers could explore to further advance in this field.